Factors predicting positive CT mesenteric angiography results in lower gastrointestinal haemorrhage prior to consideration of intra‐arterial angio‐embolisation. Issue 7 (28th March 2021) - Smith, Rohan Stuart; Tan, Stephanie Wei Jia; Heath‐Kalgutkar, Genevieve Ann; Tran, Vu Hoang; Rajagopalan, Ashray; Buckenham, Tim
Abstract: Introduction: Lower gastrointestinal haemorrhage (LGIH) is a challenging phenomenon in a comorbid, elderly population. CT mesenteric angiography (CTMA) allows localisation of the site of haemorrhage, and provides a target for interventional techniques, but the intermittent nature of LGIH makes it challenging to reliably demonstrate extravasation. This study aimed to identify objective factors that may predict scan outcomes. Methods: In this retrospective cohort study, all patients undergoing CTMA for LGIH at Monash Health from January 2011 to December 2019 ( n  = 854) were included. Baseline patient characteristics included age, bowel resection/endoscopic intervention within the past 14 days, known bowel malignancy, anticoagulant/antiplatelet use, duration of symptoms, vital signs, transfusion requirements in the past 24 h and investigation results (recent haemoglobin levels, platelet count, international normalised ratio and creatinine levels). Univariate analysis was performed, and significant factors were entered into a multivariate model. Results: The final multivariate model was statistically significant ( P  < 0.001) and consisted of bowel resection/endoscopic intervention within the past 14 days (OR = 2.15), use of antiplatelet agents (OR = 2.03), blood transfusion requirement greater than 3 units per 24 h (OR = 1.79), systolic blood pressure less than 100 mmHg (OR = 1.56) and heart rate greater than 100 beats per minute (OR = 1.52). Conclusion: The factors identified above are objective, independently associated with positive scan outcomes, readily available to radiologists and are useful for more judicious patient selection.